On-road intelligent vehicles motion planning for intelligent transportation systems - Kala, Rahul (Butterworth-Heinemann is an imprint of Elsevier, 2016)
This book is an accounting of the technology of autonomous vehicles with a special focus on navigation and planning aspects. It includes information on the use of different sensors to perceive the environment, the problem of motion planning, and the macroscopic concepts related to Intelligent Transportation Systems